Codimension theorems for complete toric varieties - Cox, D. (2005)
Let X be a complete toric variety with homogeneous coordinate ring S. In this article, we compute upper and lower bounds for the codimension in the critical degree of ideals of S generated by dim(X) + 1 homogeneous polynomials that do not vanish simultaneously on X. ©2005 American Mathematical Society.